Crime, Violence and Well-Being - Rojas, Mariano (Springer Link, 2024)
Latin Americans are exposed to high levels of violence associated to gangs, organized crime and even domestic violence. It is shown that victimization impacts negatively on the well-being of Latin Americans and that its impact is very large in the case of women. Exposure to victimization is concentrated in particular areas of the region; however, fear of crime is widely spread in many Latin American countries and it also impacts negatively on well-being. It is also shown that domestic violence has a very large impact the well-being of women.
Keywords: crime; violence; well-being; WOS(2)